Individual Factorial Structure of Biomechanical and Psychophysiological Indicators as a Basis for Determining the Fighting Style of Qualified Veteran Boxers - V.Yu. Kozin; Yu.D. Boychuk; A.V. Skaliy; R.M. Zelenskiy; V.I. Honcharenko (H.S. Skovoroda Kharkiv National Pedagogical University, 2021)
Purpose: to reveal the fighting style of veteran boxers based on the individual factor structure of psychophysiological and biomechanical indicators. Material and methods. The study involved 42 qualified veteran boxers (aged 45-50). A biomechanical analysis of the indicators of the movement speed of various points and the values ​​of the joint angles while performing a direct blow by boxers has been used as a research method. The psychophysiological method has been used to determine the time of a simple and complex reaction under standard conditions and in various testing modes. Descriptive Statistics and Factor Analysis have been applied as methods of statistical analysis. Results. Two main factors have been identified in the structure of the complex performance of qualified veteran boxers,. Factor 1 (55.063% of the total aggregate variance) is named "Speed". Factor 2 (44.937% of the total aggregate variance) stands for "Speed ​​Endurance". Individual factor structure, which is characterized by the distinctive factor "Speed ​​and Coordination Endurance" by more than 80% as well as by the marked factor "Speed" by less than 30% is considered to be a particularity of the tempo style boxers. Individual factor structure, which is characterized by the intensity of the factor "Speed" by more than 80%, and by the distinctive factor "Speed ​​and Coordination Endurance" by less than 30% is considered to be typical for the playing style boxers. The individual factor structure, which is characterized by the marked factor "Speed" by more than 50%, and by the intencity of the factor "Speed ​​and Coordination Endurance" by less than 30% is seen to be peculiar to the strength style boxers. Conclusions. It is shown that the psychophysiological features of boxers of different fighting styles are reflected in the features of the direct strike technique. The lack of speed at the beginning of the movement in tempo style boxers is supplemented and compensated by the high speed of movement. Playing style boxers are characterized by a high speed of movement at the very beginning of the strike. Strength style boxers are characterized by the gradual development of movement speed.